A Silicon Nanowire as a Spectrally Tunable Light‐Driven Nanomotor. Issue 30 (9th June 2017) - Wang, Jizhuang; Xiong, Ze; Zhan, Xiaojun; Dai, Baohu; Zheng, Jing; Liu, Jun; Tang, Jinyao
Abstract : Over the last decades, scientists have endeavored to develop nanoscopic machines and envisioned that these tiny machines could be exploited in biomedical applications and novel material fabrication. Here, a visible‐/near‐infrared light‐driven nanomotor based on a single silicon nanowire is reported. The silicon nanomotor harvests energy from light and propels itself by the self‐electrophoresis mechanism. Due to the high efficiency, the silicon nanowire can be readily driven by visible and near‐infrared illumination at ultralow light intensity (≈3 mW cm −2 ). The experimental study and numerical simulation also show that the detailed structure around the concentrated reaction center determines the migration behavior of the nanomotor. Importantly, due to the optical resonance inside the silicon nanowire, the spectral response of the nanowire‐based nanomotor can be readily modulated by the nanowire's diameter. Compared to other methods, light controlling potentially offers more freedom and flexibility, as light can be modulated not only with its intensity and direction, but also with the frequency and polarities. This nanowire motor demonstrates a step forward to harness the advantages of light, which opens up new opportunities for the realization of many novel functions such as multiple channels communication to nanorobots and controllable self‐assembly. Abstract : A visible/near‐infrared‐light‐driven nanomotor is developed based on a silicon‐nanowire solar cell and the electrophoretic mechanism. The morphology influence is experimentally and theoretically investigated, which offers a new protocol for motion maneuvering. The spectral engineering to modulate optical resonance inside the silicon wire provides a new dimension for the light‐controlled nanorobots and sheds light on their future biomedical applications.